Innovation and Productivity. (December 2013) - Thomson, Russell; Webster, Elizabeth
Abstract A country's standard of living is largely governed by economic output per capita, which corresponds closely with output per worker (labour productivity). Sustained growth in productivity over the long term requires finding ways to invest that avoid diminishing returns and this invariably means innovation and new technology.